Kinetic Regulation Engineering and In‐Situ Spectroscopy Studies on Transition‐Metal‐Based Electrocatalysts for Water Splitting. Issue 15 (10th August 2022) - Xu, Guodong; Feng, Mingyue; Wang, Shiyu; Cheng, Yu; Chen, Jiajia
Abstract: Transition metal (TM)‐based catalysts are widely studied for their unique advantages in water splitting. Despite significant progress, efficient kinetic regulation strategies for TM‐based materials in electrocatalysis and real‐time monitoring of the dynamic evolution of reaction processes are still in the initial stages. Introducing heterogeneous components into the TM‐based catalyst and forming a specific interface are beneficial to adjust the catalyst interface environment and chemical adsorption behavior, thereby accelerating the kinetic process. In this review, the kinetic improvement strategies of TM‐based electrocatalysts are timely and comprehensively summarized, including interface engineering, defect engineering, doping engineering and crystal face engineering. The main in‐situ/in‐operando characterization methods, including Raman spectroscopy, X‐ray photoelectron spectroscopy, synchrotron X‐ray absorption spectroscopy and infrared spectroscopy, are further summarized. Finally, we outline the current challenges and identify the opportunities facing this emerging area. Abstract : TM‐based catalysts for water splitting : Transition metal (TM)‐based catalysts are widely studied for their unique advantages in water splitting. This review describes the kinetic improvement strategies, including interface, defect, doping and crystal face engineering. The main in‐situ/operando characterization methods, including Raman, X‐ray photoelectron, synchrotron X‐ray absorption and infrared spectroscopy, are further summarized.